18.5% Efficiency Organic Solar Cells with a Hybrid Planar/Bulk Heterojunction. Issue 43 (12th September 2021) - Hong, Ling; Yao, Huifeng; Cui, Yong; Bi, Pengqing; Zhang, Tao; Cheng, Yongxin; Zu, Yunfei; Qin, Jinzhao; Yu, Runnan; Ge, Ziyi; Hou, Jianhui
Abstract: The donor:acceptor heterojunction has proved as the most successful approach to split strongly bound excitons in organic solar cells (OSCs). Establishing an ideal architecture with selective carrier transport and suppressed recombination is of great importance to improve the photovoltaic efficiency while remains a challenge. Herein, via tailoring a hybrid planar/bulk structure, highly efficient OSCs with reduced energy losses ( E loss s) are fabricated. A p ‐type benzodithiophene‐thiophene alternating polymer and an n ‐type naphthalene imide are inserted on both sides of a mixed donor:acceptor active layer to construct the hybrid heterojunction, respectively. The tailored structure with the donor near the anode and the acceptor near the cathode is beneficial for obtaining enhanced charge transport, extraction, and suppressed charge recombination. As a result, the photovoltaic characterizations suggest a reduced nonradiative E loss by 25 meV, and the best OSC records a high efficiency of 18.5% (certified as 18.2%). This study highlights that precisely regulating the structure of donor:acceptor heterojunction has the potential to further improve the efficiencies of OSCs. Abstract : A hybrid planar/bulk heterojunction is constructed by introducing a p‐type polymer (PTO3) and an n‐type naphthalene imide (NDI‐i8) on both sides of a mixed donor:acceptor active layer. The tailored hybrid heterojunction presents a decreased energy loss and improved efficiency. As a result, an outstanding PCE of 18.5% is achieved, which is among the top values in the field of organic solar cells.